2015
DOI: 10.17222/mit.2014.259
|View full text |Cite
|
Sign up to set email alerts
|

One-step green synthesis of graphene/ZnO nanocomposites for non-enzymatic hydrogen peroxide sensing

Abstract: In the present study, a disposable electrochemical biosensor for hydrogen peroxide (H2O2) was fabricated using a graphene/ZnO nanocomposite-modified screen-printed carbon electrode (SPCE). The adopted method is simple, cost feasible and it avoids the usage of harsh oxidants/acids during the synthesis. Graphite material was subjected to liquid-phase exfoliation with the aid of ultrasonication, without going through the intermediate graphene-oxide phase that can disrupt the pristine structure of the yield. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Li et al, 2013 [16] reported the use of green synthesized graphene|silver electroactive sensors for the detection of tryptophan. In a similar study, the one-step green synthesis of graphene|zinc nanocomposites for the nonenzymatic sensing of hydrogen peroxide is also reported [17].…”
Section: Introductionmentioning
confidence: 89%
“…Li et al, 2013 [16] reported the use of green synthesized graphene|silver electroactive sensors for the detection of tryptophan. In a similar study, the one-step green synthesis of graphene|zinc nanocomposites for the nonenzymatic sensing of hydrogen peroxide is also reported [17].…”
Section: Introductionmentioning
confidence: 89%